"A mere business affair"?Women in the social and commercial worlds of nineteenth-century Madagascar. Issue 3 (1st September 2020) - Hooper, Jane
ABSTRACT: The port of Mahajanga in northwestern Madagascar was home to a diverse commercial community during the nineteenth century. Merchants from East Africa, India and the Arabian Peninsula drew upon extensive contacts within Madagascar to obtain commodities they would then sell to Americans and Europeans. Women living in these coastal communities, however, rarely entered into Western accounts of long-distance exchanges, despite their roles as wives, traders and community members in creating the cosmopolitan economic world of Mahajanga. While not directly participating in commerce with Americans and Europeans, women engaged in agriculture and other economic activities, in addition to forming close relationships with foreigners. To offset the Western trading documentation that ignores female contributions, this article relies upon a detailed source, the diary of British merchant John Studdy Leigh, to place women more fully into this history of exchanges. By expanding our consideration of economic contributions, we can examine how women bridged the diverse economic communities in northwestern Madagascar through their marriages with foreign merchants as well as their work in supporting commerce.